Strengthening Cooperative Governance and Organizational Ethics Through Community-Based Participation - Ahmad Arfah (Aksi Kita: Jurnal Pengabdian kepada Masyarakat, 2025)
This community engagement program aimed to strengthen cooperative governance and ethical organizational practices through a participatory approach in Cemandi Village, Sidoarjo, East Java. Village-level cooperatives often face challenges related to accountability, member participation, and underdeveloped organizational structures. To address these issues, the program implemented three key activities: a simulation of the Annual General Meeting (AGM), a workshop on developing internal bylaws and cooperative structure, and a community dialogue on local ethical values and social auditing practices. The implementation method combined participatory facilitation, community-based training, and value-based dialogue. The results demonstrated an increase in organizational literacy among participants, the formulation of cooperative bylaws, and the execution of an AGM simulation that reflected democratic principles. Tangible outcomes included a prototype of a citizen-based social audit tool, a draft of cooperative bylaws, and strengthened member participation. The findings indicate that participatory methods are effective in enhancing cooperative governance rooted in community values and collective ethics.